Penerapan Model Pembelajaran Project Based Learning (PJBL) untuk Meningkatkan Hasil Belajar Matematika Siswa SDN No.165 Inpres Al-Qamar - Khairunnisa, Irfina (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2024)
In this research, namely, the learning outcomes of class III students at SD Negeri No. 165 inpres Al-Qamar who have not reached the minimum completion standards set. This research aims to improve the learning process and outcomes by applying the Project Based Learning (PjBL) learning model. This research uses a qualitative approach and the type of research is classroom action research (PTK). This research was carried out in 2 cycles, each cycle consisting of 4 stages which included planning, implementation, observation and reflection. To determine the percentage level of student learning processes and outcomes, researchers used observation sheets and evaluation tests in each cycle. The subjects in this research were teachers and students of class III of SD Negeri No. 165 inpres Al-Qamar in the 2022/2023 academic year. The data analysis technique used is a qualitative data analysis technique. Based on data obtained from research results, applying the Project Based Learning (PjBL) learning model can improve the learning process and student learning outcomes in class III of SD Negeri No. 165 inpres Al-Qamar.